A study on approximate controllability of linear impulsive equations in Hilbert spaces - Mahmudov, Nazim I. (Taylor & Francis Ltd, 2024)
In this paper, we study an approximate controllability for the impulsive linear evolution equations in Hilbert spaces. We give a representation of solution in terms of semigroup and impulsive operators. We present the necessary and sufficient conditions for approximate controllability of linear impulsive evolution equation in terms of impulsive resolvent operator. An example is provided to illustrate the application of the obtained results.
Keywords: Approximate controllability; existence and uniqueness; impulsive systems